Role of Dipolar and Nondipolar Components of the T Wave in Determining the T Wave Residuum in an Isolated Rabbit Heart Model - Biagetti, Marcelo (2004)
Introduction: Repolarization heterogeneity has been shown to constitute a substrate for malignant ventricular arrhythmias. Noninvasive measurement of abnormal repolarization through assessment of QT interval dispersion from the resting standard 12-lead ECG initially had shown promise in assessing arrhythmia risk but was challenged recently. The relative T wave residuum (TWR) has been proposed recently to reflect regional repolarization dispersion more accurately. We analyzed the role played by the dipolar and nondipolar components in determining TWR. Methods and Results: Singular value decomposition was applied to the repolarization signals obtained from isolated rabbit hearts using a 5 × 8 array multielectrode recording system during premature beats (N = 11) and after d-sotalol (N = 9) exposure. Both the dipolar and nondipolar components of the T wave increased significantly during premature stimulation and after d-sotalol exposure. The relative TWR decreased significantly during premature stimulation but did not change after d-sotalol. Changes in the dipolar and nondipolar components of the second half of the T wave were significantly greater than those corresponding to the first half during premature stimulation, and a significant correlation was observed between the nondipolar components of the second half of the T wave and the Tpeak?end interval. Conclusion: Conditions exist during which both the dipolar and nondipolar components can change simultaneously. Under these conditions, the relative TWR may not reflect regional heterogeneity of repolarization with accuracy. The nondipolar components of the second half of the T wave can be linked to assessment of the transmural dispersion of repolarization.